Effects of continuous cropping on soil metabolomics and rhizosphere bacterial communities in Panax quinquefolius L. - Song, Jian; He, Qing; Cao, Kuo; Song, Xiliang; Zeng, Qiangcheng (Frontiers in Microbiology, 2025)
IntroductionContinuous cropping obstacles (CCOs) due to long-term monoculture have emerged as a pervasive challenge in contemporary agriculture worldwide. The practices of CCOs are the primary causes of restraining the Panax quinquefolius L. (P. quinquefolius) growth, whereas its underlying microbial mechanisms have not been fully elucidated.MethodsWe investigated the effects of CCOs on soil physicochemical properties, enzyme activities, microbial community composition, and metabolite profiles in the rhizosphere of P. quinquefolius cultivated continuously for one, two, three, and four consecutive years (designated as CC1, CC2, CC3, and CC4, respectively) without crop rotation. Rhizosphere soil samples were collected from fields with different years of CCOs and analyzed for physicochemical properties and enzyme activities. Microbial community composition was assessed using Illumina high-throughput sequencing, and metabolite profiles were analyzed using non-targeted metabolomics (UPLC-MS/MS).ResultsSignificant decreases were observed in soil pH (12.2–28.0%), cation exchange capacity (42.6–65.5%), organic matter (8.7–27.3%), total nitrogen (7.6–27.8%), and ammonium (NH4+) content (16.9–56.6%) with an increasing number of continuous cropping years. Enzymatic activities, including urease, invertase, alkaline phosphatase, catalase, protease, and polyphenol oxidase, were also reduced. The occurrence of CCOs decreased bacterial richness and number but increased bacterial diversity. Key microbial biomarkers were shifted from Gemmatimonadota, Actinobacteriota, and Proteobacteria to Acidobacteriota, Chloroflexi, and WPS-2 with P. quinquefolius CCOs. Consequently, the number of beneficial microorganisms decreased, whereas the number of pathogenic microorganisms increased. Non-targeted metabolomic profiling showed significant enantioselectivity in phenylpropanoid biosynthesis and pyrimidine metabolism. Time-series analysis revealed a decrease in metabolites classified as lipids and lipid-like molecules and an increase in organic acids, derivatives, phenylpropanoids, and polyketides with continuous cropping. Partial least squares-path modeling identified reduced soil enzymatic activity due to CCOs as the primary factor regulating soil bacterial communities and metabolites.SignificanceThese findings offer new insights into the microecological mechanisms of CCOs in P. quinquefolius, aiding in controlling pathogenic bacteria and maintaining soil health in agricultural systems.Conclusion and prospectsP. quinquefolius CCOs significantly alter soil physicochemical properties, microbial community structure, and metabolite profiles, leading to reduced soil fertility and increased prevalence of soil-borne diseases. Future research should focus on exploring sustainable agricultural practices, such as crop rotation and soil amendments, to mitigate these adverse effects and improve the long-term viability of P. quinquefolius cultivation.